2021
DOI: 10.3390/v13050870
|View full text |Cite
|
Sign up to set email alerts
|

Type II Grass Carp Reovirus Infects Leukocytes but Not Erythrocytes and Thrombocytes in Grass Carp (Ctenopharyngodon idella)

Abstract: Grass carp reovirus (GCRV) causes serious losses to the grass carp industry. At present, infectious tissues of GCRV have been studied, but target cells remain unclear. In this study, peripheral blood cells were isolated, cultured, and infected with GCRV. Using quantitative real-time polymerase chain reaction (qRT-PCR), Western Blot, indirect immunofluorescence, flow cytometry, and transmission electron microscopy observation, a model of GCRV infected blood cells in vitro was established. The experimental resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…To examine mRNA distribution in blood cells, grass carp blood was collected by caudal venipuncture with a syringe that contain 5–10% 0.5‐M EDTA (pH 8.0). The peripheral blood erythrocytes, leukocytes, and thrombocytes were isolated using a fish peripheral blood platelet separation kit (P1740, Solarbio, Beijing, China) according to manufacturer instructions (Yang & Su, 2021) ( n = 4). Total RNA was isolated and reverse transcribed for qRT–PCR.…”
Section: Methodsmentioning
confidence: 99%
“…To examine mRNA distribution in blood cells, grass carp blood was collected by caudal venipuncture with a syringe that contain 5–10% 0.5‐M EDTA (pH 8.0). The peripheral blood erythrocytes, leukocytes, and thrombocytes were isolated using a fish peripheral blood platelet separation kit (P1740, Solarbio, Beijing, China) according to manufacturer instructions (Yang & Su, 2021) ( n = 4). Total RNA was isolated and reverse transcribed for qRT–PCR.…”
Section: Methodsmentioning
confidence: 99%
“…GCRV-II easily breaks through the thin monolayer flattened epithelial cells in branchial lamella and enters the blood circulation, which is fast in gill, thus, virus is transported to other tissues, so virus can be detectable at 5 min by semi-qRT-PCR but detectable at 45 min by WB. Previous study indicated that GCRV-II can infect leukocytes [22]. Thus, GCRV-II can pass the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 96%
“…Nostril, olfactory bulb, olfactory tract, and brain tissues of immersion infected grass carp were fixed with 2.5% glutaraldehyde in a 0.1 M phosphate buffer (pH 7.2) at 4°C for 24 h to observe the virus particles. Ultrathin sections were prepared as previously described [22]. Images were viewed on an HT-7700 TEM (Hitachi, Japan).…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…GCRV-II easily breaks through the thin monolayer flattened epithelial cells in branchial lamella and enters blood circulation, which is fast in gills, thus, the virus is transported to other tissues; hence, the virus can be detectable at 5 min via semi-qRT-PCR but detectable at 45 min via WB. Previous study has indicated that GCRV-II can infect leukocytes [ 24 ]. Thus, GCRV-II can pass the blood–brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…The nostril, olfactory bulb, olfactory tract, and brain tissues of immersion infected grass carp were fixed with 2.5% glutaraldehyde in a 0.1 M phosphate buffer (pH 7.2) at 4 °C for 24 h to observe the virus particles. Ultrathin sections were prepared as previously described [ 24 ]. Images were viewed on an HT-7700 TEM (Hitachi, Japan).…”
Section: Methodsmentioning
confidence: 99%